Key drug discovery challenges in cardiovascular medicine - Swerdlow, Dan; Holmes, Michael V. (Henry Stewart Talks, 2014)
Conventional therapeutic targets in CVD, Identifying new targets (GWAS and association analysis), Validating new targets (Mendelian randomisation; IL6R, CHD and tocilizumab; sPLA2 inhibition and CHD prevention), Avoiding adverse effects (The ILLUMINATE trial, Torcetrapib and blood pressure), Making better use of existing drugs (Pharmacogenetics of Clopidogrel and CYP2C19), New approaches & drug development